2022
DOI: 10.1101/2022.08.09.22278580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost and cost-effectiveness of Hepatitis C virus self-testing in four settings: an economic evaluation

Abstract: Introduction: Globally, there are approximately 58 million people with chronic hepatitis C virus infection (HCV) but only 20% have been diagnosed. HCV self-testing (HCVST) could reach those who have never been tested and increase access and uptake of HCV testing services. We compared cost per HCV diagnosis or cure for HCVST versus facility-based HCV testing services. Methods: We used a decision analysis model with a one-year time horizon to examine the key drivers of economic cost per diagnosis (viraemic infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…8 Most of the empirical evidence on the cost of selftesting programmes originates from the human immunodeficiency virus (HIV) self-testing literature, 6 9 10 and more recently from hepatitis C virus (HCV) self-testing. 11 Studies have demonstrated the relative cost of different methods for rollout of HIV self-testing and found, broadly, that there are multiple ways of successfully distributing HIV self-testing, depending on the budget and desired outcome. For HIV self-testing, expansion of testing beyond primary healthcare clinics yielded a net increase in life years saved across all distribution models.…”
Section: Open Accessmentioning
confidence: 99%
“…8 Most of the empirical evidence on the cost of selftesting programmes originates from the human immunodeficiency virus (HIV) self-testing literature, 6 9 10 and more recently from hepatitis C virus (HCV) self-testing. 11 Studies have demonstrated the relative cost of different methods for rollout of HIV self-testing and found, broadly, that there are multiple ways of successfully distributing HIV self-testing, depending on the budget and desired outcome. For HIV self-testing, expansion of testing beyond primary healthcare clinics yielded a net increase in life years saved across all distribution models.…”
Section: Open Accessmentioning
confidence: 99%
“…A cost-effectiveness modelling study was conducted to identify drivers of cost of testing or HCV cure with introduction of HCVST across four countries 14. The cost-effectiveness model suggested that HCVST is likely to be costlier than standard testing but will reach more people for testing 14…”
Section: Main Sources Of Evidence For Hcvst Guidelines Development An...mentioning
confidence: 99%